Énoncés capacitifs et constructions à sujet locatif : quel alignement syntaxe-sémantique ? - Christelle Lacassain; Caroline Marty (Anglophonia)
The present paper focuses on two constructions – capacitive (e.g. The main dining room seats 65) and setting-subject (e.g. The reign of Charles II saw the end of the great Forest courts) constructions – which are comparable in more than one way. The verbs under study (seat and sleep, the two most frequent verbs in capacitive sentences; see and witness, the only two ‘perception’ verbs featuring in setting-subject constructions) prototypically license an animate subject whereas in these less prototypical constructions, the subject has an inanimate referent, either spatial or temporal (the latter only in setting-subject constructions). The alignment between syntactic function and semantic role is not prototypical, as the subject referent is neither an agent nor an experiencer, but denotes, at first sight, a place or a temporal period. Finally, the two types of sentences abstract away from the expression of a concrete situation experienced by a human animate, originally denoted by the verbs concerned.The study addresses the mechanisms at work in both types of constructions. It shows that not only does the difference in syntax-semantics alignment between prototypical and non-prototypical sentences allows for the emergence of a new, abstract verbal meaning, but also that there is a logic of continuity between prototypical (She slept well or We saw a car with only one headlight on) and non-prototypical sentences. By analysing the syntax-semantics alignment present in these two types of sentences, we can first identify the deviations present at the syntax-semantics interface in capacitive and setting-subject constructions, and then attempt to categorise the type of alignment at work in such constructions, in which the thematised locative constituent is neither a typical subject nor a typical topic; it is conceived of as a participant in the process, rather than as a mere circumstance. In the light of such analyses, the motivation for this specific syntax-semantics alignment and the topicalisation of the locative is revealed, as is the meaning at work in both types of constructions.